2009
DOI: 10.1002/mrm.22123
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic iron oxide nanoparticles as a dual imaging probe for targeting hepatocytes in vivo

Abstract: Hepatocyte-specific targeting agents are useful for evaluation of the hepatocytic function and the monitoring of disease progress. Superparamagnetic iron oxide nanoparticles (SPION) bearing terminal galactose groups exhibit a high affinity for the asialoglycoprotein receptor on the hepatocyte surface. In this study, we synthesized and characterized the dual probe SPION detectable by both nuclear and MR imaging modality for specifically targeting hepatocytes in vivo. SPION with 12-nm diameter were functionalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 18 publications
2
44
0
Order By: Relevance
“…SPIONs having amino groups on their surface are quickly captured by phagocytic cells such as macrophages in the liver and spleen (33,34). We used GA to modify the ATP@SPIONs so as to diminish phagocytosis by the reticuloendothelial system and adsorption of plasma proteins on the particle's surface.…”
Section: Discussionmentioning
confidence: 99%
“…SPIONs having amino groups on their surface are quickly captured by phagocytic cells such as macrophages in the liver and spleen (33,34). We used GA to modify the ATP@SPIONs so as to diminish phagocytosis by the reticuloendothelial system and adsorption of plasma proteins on the particle's surface.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PI is a nuclei staining dye, which can pass through only the disordered areas of the dead cell membrane and intercalates with the DNA double helix of the cell to emit a red fluorescence (excitation: 535 nm, emission: 617 nm). After 3 days of culture, green fluorescence was observed in the cells cultured in the presence and absence of the GL, suggesting good biocompatibility of GL (Lee et al 2009). Evaluation of intracellular uptake…”
Section: Evaluation Of Cytotoxicitymentioning
confidence: 99%
“…Furthermore, this molecule readily binds to carbohydrates such as galactose, mannose, and arabinose, which can thereby serve as effective liver-targeted drug delivery systems (Yang et al 2010;Cho et al 2008). Jeong et al demonstrated the use of galactose-conjugated superparamagnetic iron oxide nanoparticles (SPIONs) as a hepatocytetargeted dual contrast agent (nuclear imaging/MRI) in a mouse model (Lee et al 2009). This proved to be important as hepatocyte-selective imaging was needed for the evaluation of hepatocyte function under certain clinical conditions such as partial liver transplant or hepatitis, as well as for monitoring disease progress.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many investigators have synthesized RGD molecular probes to image tumors and have provided a promising future for early diagnosis of hepatocellular carcinoma. [5][6][7] A further method involves targeting tumor cell receptors, whereby ligands or antibodies corresponding to biologic markers expressed by hepatocellular carcinoma cells are coupled with an MR contrast agent to synthesize a molecular MR probe, which can be connected to or incorporated into hepatocellular carcinoma cells using the principle of antigenantibody binding. The tumor cells can then be imaged using this probe and an MR scanner.…”
Section: Introductionmentioning
confidence: 99%